Analysis of Dengue Hemorrhagic Fever Prevention in Indonesian Coastal Communities: A review - Rahma Fanti; Andi Marhana (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains a significant public health issue, characterized by an increasing number of cases and a progressively wider geographic distribution. Preventive behavior against dengue in coastal communities remains suboptimal. Most coastal regions exhibit similar environmental characteristics, including the accumulation of plastic waste and other discarded materials that serve as potential breeding grounds for Aedes aegypti mosquitoes. Objectives: To analyze current and effective strategies for preventing DHF, particularly in coastal communities where the disease burden remains high. Methods: This study employed a literature review method using secondary data sourced from Google Scholar and PubMed databases, focusing on publications from 2019 to 2025 (the last six years). Results: The literature review indicates that dengue prevention efforts are commonly implemented through community empowerment strategies, including socialization, health education, and training activities. A key component of these strategies is the 3M Plus (3M+) approach, which involves draining water containers, closing or burying unused items, and recycling materials to eliminate mosquito breeding sites. These interventions aim to reduce the population of Aedes aegypti, the primary vector of the dengue virus. Conclusion: Community empowerment is an effective approach to enhance public knowledge and participation in dengue prevention. The implementation of the 3M Plus (3M+) strategy draining, covering/burying, and recycling is essential to limit mosquito breeding and thereby reduce dengue transmission. Furthermore, the availability of a dengue vaccine provides an additional preventive measure that can further strengthen public health efforts in combating DHF. Keywords: Aedes aegypti, community empowerment, vector control, coastal environment, dengue vaccine, Indonesia